2011
DOI: 10.1007/s11483-010-9199-3
|View full text |Cite
|
Sign up to set email alerts
|

Fibril Formation of Bovine α-Lactalbumin Is Inhibited by Glutathione

Abstract: The current research is aimed at exploring the inhibitory effect of glutathione on fibril formation of an important four disulfide bond-containing whey protein, α-lactalbumin. Through numerous spectroscopic techniques and transmission electron microscopy, we found that the inhibition of amyloid formation of α-lactalbumin was dependent on the glutathione concentration and fibrillation was significantly attenuated in the presence of 5 mM glutathione. Moreover, the data from the measurements using 4,4′-dithiodipy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The impact of food constituents on fibril formation. Glutathione, crocin, and safranal can inhibit amyloid formation of calcium ion depleted α-LA at acidic pH (Ebrahim-Habibi, Amininasab, Ebrahim-Habibi, Sabbaghian, & Nemat-Gorgani, 2010; Wang, Liu, Wen, & Wang, 2011).…”
Section: α-Lactalbuminmentioning
confidence: 99%
“…The impact of food constituents on fibril formation. Glutathione, crocin, and safranal can inhibit amyloid formation of calcium ion depleted α-LA at acidic pH (Ebrahim-Habibi, Amininasab, Ebrahim-Habibi, Sabbaghian, & Nemat-Gorgani, 2010; Wang, Liu, Wen, & Wang, 2011).…”
Section: α-Lactalbuminmentioning
confidence: 99%
“…The results indicated that the best operational conditions produced WPF to remove the maximum quantity of mercury and chromium alone and mixed. Similar conditions (i.e., 75~120 • C, pH 2~3.5, low salt content < 0.1 M and 60~85 • C, pH 2) are commonly used to form amyloid fibrils of β-Lactoglobulin [29,41,51,52] and α-lactalbumin [48,53,54], respectively. Loveday et al [55] concluded that a protein sequence exposed to different conditions can generate a variety of a fibrillar aggregations.…”
Section: Preparation Of Whey Protein Fibrilsmentioning
confidence: 99%
“…Glutathione is an endogenous antioxidant that can regenerate oxidized form of ascorbic acid and participate in along with superoxide dismutase in the antioxidative defense system of body (Poljask & Milisav, 2014). Wang, Liu, Wen, and Wang (2011) studied the effect of glutathione on fibrillation process of a-lactalbumin and showed that fibrils formation at pH 2.2 and 55 C could be effectually retarded by glutathione. Glutathione function was correlated with diminution of the disulfide bridges of protein and the suppression of fibril formation was extremely reliant on glutathione concentration.…”
Section: Inhibitors Of Nanofibrillationmentioning
confidence: 99%